The Olympic Games and the development of sports for the disabled in China - Luo, Y.; Wan, H. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: With the increasing promotion of the Olympic Games throughout the world, the Special Olympic Games for people with disability attracts the attention of the whole world and continues to develop. According to statistics there are currently 500 million disabled people in the world, with 60 million residing in China. It is estimated that an additional 20 thousand people become, or are born, disabled every day. Therefore, it is a priority to improve the sports status of the disabled, improve training levels, gain increased commitment from the government, and enhance the facilities available. This focus will encourage the formation of a positive social environment and promote the sports development of the disabled in an equitable and ethical way. Methods Through questionnaires, interviews and literature review the current development situation of the disabled was assessed and analyzed. Results The main factors identified by the respondents in restricting exercise oportunities for the disabled in China included in order of priority: no subsistence allowances; no finances; no fields or equipment for the disabled; lack of organisation. Conclusions At present in China, the opportunities for sports and exercise participation for the disabled is lacking. However, due to the 2008 Olympic Games in Beijing, the government will have the opportunity to promote the improvement and development of sports for the disabled. Encouragement of participation in sports for the disabled is necessary to promote and realize the value of activity, foster healthy competition as well as access to physical activity being a human right. Participating in sports can help the disabled live a normal life, and establish the mind-set necessary for this group of people to communicate with society.